An radio-frequency identification security authentication mechanism for Internet of things applications - Zhen-Yu Wu (International Journal of Distributed Sensor Networks)
Among various Internet of things technologies, radio-frequency identification technology is currently one of the most critical. Radio-frequency identification tags store messages collected by the reader; thereafter, the messages are transmitted to the backend system for processing and analysis, thereby forming a huge knowledge network and achieving the objective of intelligent management of objects. However, the personal information and privacy exposure, malicious tracking, and counterfeiting behaviors remain the unresolved issues in the security area. In this study, we developed a matrix-based authentication protocol that was protected by Hill Cipher Hard Problem by which it can provide confidentiality, anti-counterfeiting, and users’ location privacy. In addition, the identity verification of this scheme based on matrix needs only once matrix multiplication operation to know the outcome. Consequently, the analysis of computational complexity demonstrated that our scheme can handle the mass data from the reader, thereby achieving system extensibility.